DIMENSI KOGNITIF TRENDS IN INTERNATIONAL MATHEMATICS AND SCIENCE STUDY (TIMSS): ANALISIS SOAL PADA BUKU MATEMATIKA KURIKULUM MERDEKA KELAS VIII - Septia_Marcella; Bambang Sri Anggoro; Siska Andriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low achievement of Indonesian students in international assessments such as the Trends in International Mathematics and Science Study (TIMSS) remains a significant concern in the education sector. One potential factor is the insufficient quality of evaluation questions in textbooks, particularly in measuring higher-order thinking skills. The Grade VIII Mathematics student book under the Merdeka Curriculum, introduced as part of recent curriculum reforms, is expected to incorporate questions that reflect all TIMSS cognitive dimensions: knowing, applying, and reasoning. However, prior studies have consistently noted a dominance of questions within the knowing domain.This study aims to analyze the practice questions in the Grade VIII Mathematics student book—specifically on the topic of exponents—based on the TIMSS cognitive dimensions. Employing a qualitative descriptive method, the research utilizes documentation techniques and an expert-validated classification instrument. The findings reveal an imbalance in question distribution, with a majority categorized under the knowing domain, while applying and reasoning domains are considerably underrepresented. These results suggest that the textbook questions do not yet adequately foster students’ critical and analytical thinking skills in line with international benchmarks. Accordingly, a more balanced and comprehensive development of questions is recommended to better support the competency goals of the Merdeka Curriculum.